Influence of dispersion method of LaF3 in ZrB2-based ceramics on high-temperature oxidation resistance. Issue 12 (15th June 2021) - Hu, Jing; Li, Qi; Xie, Jianliang; Liu, Peng; Jiang, Shaoliang; Wang, Xin; Yin, Liangjun; Zhang, Li; Lu, Haipeng; Zhang, Linbo; Deng, Longjiang
Abstract: The high-temperature applications of zirconium diboride (ZrB2 ) ceramics are hindered due to their easy initial oxidation at temperature around 700 °C. Although mixing and coating methods have been introduced to enhance the oxidation resistance of ZrB2 -based ceramics, their thorough comparative analysis still demands a more systematic exploration. Herein, spark plasma sintered ZrB2 @20 vol% LaF3 and ZrB2 +20 vol% LaF3 ceramics prepared by coating and mixing powders, respectively, were used to study the influence of dispersion method of LaF3 on their oxidation resistance. After oxidation at 1000 °C for 4 h, a thin oxide layer ( 25 μm) and low weight gain (9%) confirmed the superior oxidation resistance of ZrB2 +20 vol% LaF3 over ZrB2 @20 vol% LaF3, which could be attributed to the formation of a dense surface layer due to the self-healing mechanism. In turn, the poor oxidation resistance of ZrB2 @20 vol% LaF3 was caused by the "anchoring" of LaF3 cladding layer and locally-coated ZrB2 particles, which led to the in situ reactions and formation of a porous oxide scale ( 400 μm). Finally, the discrepant oxidation resistance mechanisms of ZrB2 –LaF3 ceramics obtained by different dispersion methods of LaF3 were proposed.